Heterobimetallic Zn2+/Co2+ Monocarboxylates as Precursors for ZnO Microparticles Doped with Cobalt and its Photocatalytic Activity in Methyl Orange Oxidation - Correa, Hélder Inocêncio Ferreira; Ramalho Jr, Ralf Ricardo; Oliveira, Adhimar Flávio; Lisboa, Fabio da Silva (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
In this work, zinc oxide microparticles doped with cobalt were prepared from two novel layered heterobimetallic monocarboxylates as precursors to obtain uniform shape and size oxide particles, aiming for a photocatalytic removal of methyl orange. Both monocarboxylates produced ZnO doped with Co2O3 after calcination at 700 or 900 °C, in 7 or 12 hours. The particles formed by the laurate precursor presented rectangular prisms shaped, while those formed from stearate were sphere-like particles. All particles ranged from 0.1 to 0.9 μm size, with a direct bandgap of 2.2 to 2.6 eV and an indirect bandgap of 0.25 to 1.70 eV. The ZnO/Co prepared presented photocatalytic activity on methyl orange photodegradation. The solid prepared by the laurate precursor showed a photodegradation rate of 0.00185 min-1, while the one obtained from the stearate precursor presented a photodegradation rate of 0.00860 min-1, eight times greater. These results show that the material may be very useful in removing dyes from water samples. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).